A novel HLA‐B*18:80 allele identified by SBT typing in an Italian bone marrow volunteer donor. (5th February 2014) - Lochmann, E.; Frison, S.; Longhi, E.; Moscetti, A.; Vecchiato, C.
Summary A novel allele, officially named B*18:80, was detected in a Caucasoid individual by polymerase chain reaction–sequence‐specific primers and SBT. The new allele differs from B*18:01:01 at two nucleotidic positions in codon 24 at exon 2.